beta-defensins and the epididymis: contrasting influences of prenatal, postnatal, and adult scenarios - Ribeiro, Camilla M.; Silva, Erick J. R. [UNESP]; Hinton, Barry T.; Avellar, Maria Christina W. (Medknow Publications & Media Pvt Ltd, 2016)
beta-defensins are components of host defense, with antimicrobial and pleiotropic immuno-modulatory properties. Research over the last 15 years has demonstrated abundant expression of a variety of -defensins in the postnatal epididymis of different species. A gradient of region- and cell-specific expression of these proteins is observed in the epithelium of the postnatal epididymis. Their secretion into the luminal fluid and binding to spermatozoa as they travel along the epididymis has suggested their involvement in reproduction-specific tasks. Therefore, continuous attention has been given to various -defensins for their role in sperm function and fertility. Although -defensins are largely dependent on androgens, the underlying mechanisms regulating their expression and function in the epididymis are not well understood. Recent investigation has pointed out to a new and interesting scenario where -defensins emerge with a different expression pattern in the Wolffian duct, the embryonic precursor of the epididymis, as opposed to the adult epididymis, thereby redefining the concept concerning the multifunctional roles of -defensins in the developing epididymis. In this review, we summarize some current views of -defensins in the epididymis highlighting our most recent data and speculations on their role in the developing epididymis during the prenatal-to-postnatal transition, bringing attention to the many unanswered questions in this research area that may contribute to a better understanding of epididymal biology and male fertility.
Keywords: androgens; embryogenesis; epididymis; organogenesis; beta-defensins